2018
DOI: 10.1016/j.ic.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Greatest fixed points of probabilistic min/max polynomial equations, and reachability for branching Markov decision processes

Abstract: We give polynomial time algorithms for quantitative (and qualitative) reachability analysis for Branching Markov Decision Processes (BMDPs). Specifically, given a BMDP, and given an initial population, where the objective of the controller is to maximize (or minimize) the probability of eventually reaching a population that contains an object of a desired (or undesired) type, we give algorithms for approximating the supremum (infimum) reachability probability, within desired precision ǫ > 0, in time polynomial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Since the publication of the conference version of this paper [19] 9 , we have obtained several subsequent results in papers that build on and extend this work. Specifically, in [18] and [20] we have studied more general branching Markov decision processes, which extend BPs with a controller that can take actions to influence the reproduction probabilities with the goal of maximizing or minimizing the extinction probability, and we studied also their associated max/min probabilistic polynomial systems of equations (max/minPPSs) which involve also a max or min operator. We have shown that a Generalized Newton's method, which involves linear programming in each iteration, can be used to compute both the least and greatest fixed point solutions of such systems of equations in polynomial time to desired precision (in the standard Turing model of computation).…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of the conference version of this paper [19] 9 , we have obtained several subsequent results in papers that build on and extend this work. Specifically, in [18] and [20] we have studied more general branching Markov decision processes, which extend BPs with a controller that can take actions to influence the reproduction probabilities with the goal of maximizing or minimizing the extinction probability, and we studied also their associated max/min probabilistic polynomial systems of equations (max/minPPSs) which involve also a max or min operator. We have shown that a Generalized Newton's method, which involves linear programming in each iteration, can be used to compute both the least and greatest fixed point solutions of such systems of equations in polynomial time to desired precision (in the standard Turing model of computation).…”
Section: Discussionmentioning
confidence: 99%
“…(See also [3], where the two-player stochastic game version of qualitative reachability problems was considered.) We remark that in the case of BMDPs, the supremum reachability probability is 1 if and only if there is a strategy that achieves it, and this can be decided in polynomial time [14]. However, note that the equivalence between 1-RMDP and BMDP with respect to the extinction probability does not carry over to the reachability probability, for essentially the same reason that it does not hold in the reward model with 0 rewards.…”
Section: → })mentioning
confidence: 95%
“…Players can use whatever strategy they wish to optimize a given objective. See [17,13,14] for more on these models. We mention that the results of this paper yield directly a polynomial time algorithm, given a BMDP, for computing the optimal (maximum or minimum) expected number of descendants of a given type for an object of a given type.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations